Analisa Gaya Pada Sistem KemudiTyperecirculating Ball - Riawan, Feri Agus; , Supriyono, ST.MT.Ph.D (2016)
ABSTRACTION Steering system serves to regulate or control the direction of motion of the vehicle the driver's liking. Judging from the power steering system used divided into two manual steering systems and power steering, while the manual steering system itself is divided into two recirculating ball type and rack & pinion. This final project aims to determine how large a force that occurs in the steering system is recirculating ball type that occurs in particular style on the wheel when the car is deflected and style dbutuhkan to turn the steering wheel when the car in a certain position. In the calculation process there are some limitations problems that must be determined first before completing the analysis of the discussion, namely, the center point of the vehicle's weight (center of gravity) has determined its position and assumed to be within 1000mm from the ground, the angle steer the average front wheel 50 °, angle slippage each wheel is ignored, the value of the static friction coefficient is assumed at 0,6, F max = F tierod, the coefficient of kinetic friction ( ) = 0.4 (obtained from books vehicle dynamics). The results of calculation analysis obtained the following results: the forces acting on each wheel are each = 5715,2 N, = 1642,3 N, = 14715 N, the maximum frictional force that occurs at each wheel is = 3411,12 N, a force to rotate static or dynamic steering, respectively = 46,8 N, = 31,2 N, maximum speed ( ) are allowed at the time of turn is 16 km/ hour. Keywords: Steering system, Recirculating ball, the force acting